2016
DOI: 10.1111/gcbb.12328
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of management practices on bioenergy feedstock yield and economic feasibility on Conservation Reserve Program grasslands

Abstract: Perennial grass mixtures planted on Conservation Reserve Program (CRP) land are a potential source of dedicated bioenergy feedstock. Long-term nitrogen (N) and harvest management are critical factors for maximizing biomass yield while maintaining the longevity of grass stands. A six-year farm-scale study was conducted to understand the impact of weather variability on biomass yield, determine optimal N fertilization and harvest timing management practices for sustainable biomass production, and estimate econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Conservation Reserve Program lands may represent an important resource for producing cellulosic bioenergy feedstock without competing for land with food, feed, and fiber production. Our long‐term field study during 2008–2013 indicates that the annual biomass yield was 2.82 Mg ha −1 for warm‐season mixture CRP land and 5.10 Mg ha −1 for cool‐season mixture CRP land under best management practices (Anderson et al ., ). Nitrogen fertilization is the key agronomic management factor determining biomass yield on CRP land, but applications of 112 kg N ha −1 are probably not the best economic practice with such low biomass production.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Conservation Reserve Program lands may represent an important resource for producing cellulosic bioenergy feedstock without competing for land with food, feed, and fiber production. Our long‐term field study during 2008–2013 indicates that the annual biomass yield was 2.82 Mg ha −1 for warm‐season mixture CRP land and 5.10 Mg ha −1 for cool‐season mixture CRP land under best management practices (Anderson et al ., ). Nitrogen fertilization is the key agronomic management factor determining biomass yield on CRP land, but applications of 112 kg N ha −1 are probably not the best economic practice with such low biomass production.…”
Section: Discussionmentioning
confidence: 97%
“…Nitrogen fertilization is the key agronomic management factor determining biomass yield on CRP land, but applications of 112 kg N ha −1 are probably not the best economic practice with such low biomass production. Therefore, it is very important to conduct economic analyses based on rental payments, input costs including fertilizer, biomass yield, and price received for biomass (Anderson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, we found that N fertilization significantly increased SOC and TN in both SG and GG croplands. This was likely due to the minimal management and mechanical disturbance in our plots, which minimized soil decomposition due to less exposure of below surface soil to air, consequently diminished soil C and N losses in favor of soil C and N accumulations in perennial bioenergy feedstock grasslands [56][57][58]. In Table 1.…”
Section: N Fertilization Enhanced Soc and Tn Concentrations In Sg And Ggmentioning
confidence: 99%
“…We refer readers to Anderson et al. () for a study regarding using CRP land as a potential source of biomass production.…”
mentioning
confidence: 99%